Famous in a small town [large type] - Shipman, Viola (Center Point Large Print, 2023)
"For most of her eighty years, Mary Jackson has endured the steady invasion of tourists, influencers and real estate developers who have discovered the lakeside charm of Good Hart, Michigan, waiting patiently for the arrival of a stranger she's believed since childhood would one day carry on her legacy -- the Very Cherry General Store. Like generations of Jackson women before her, Cherry Mary, as she's known locally, runs the community hub -- part post office, bakery and sandwich shop -- and had almost given up hope that the mysterious prediction she'd been told as a girl would come true and the store would have to pass to . . . a man. Becky Thatcher came to Good Hart with her ride-or-die BFF to forget that she's just turned forty with nothing to show for it. Ending up at the general store with Mary is admittedly not the beach vacation she expected, but the more the feisty octogenarian talks about destiny, the stronger Becky's memories of her own childhood holidays become, and the strange visions over the lake she was never sure were real. As she works under Mary's wing for the summer and finds she fits into this quirky community of locals, she starts to believe that destiny could be real, and that it might have something very special in mind for Becky . . "--